Influence of grafted β-cyclodextrin on the sorbing activity of silica gel to ions of toxic metals - Belyakova, L. A.; Belyakov, V. N.; Vasilyuk, S. L.; Shvets, O. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The uptake of cations of toxic metals (cadmium, lead, and copper) and oxyanions from nitrate, phosphate, and arsenate aqueous solutions by silica chemically modified with β-cyclodextrin is studied. It is proved that the sorption process involves the simultaneous formation of surface supramolecular structures "β-cyclodextrin — oxyanion" and mixed complexes of metal cations with the side functional groups of grafted β-cyclodextrin. It is found that the adsorption of cations correlates with the electronegativity of chemical elements, and the adsorption of oxyanions — with the complementarity of their sizes to parameters of the internal cavity of the cyclic oligosaccharide.